Complement C3 as a potential NAFLD predictor in an Egyptian cohort with diabetes and/or obesity - Halla M. Ragab; Nabila Abd El Maksoud; Mona A. Amin; Wafaa Abd Elaziz (SpringerOpen, 2022)
Highlights NAFLD nowadays becomes a challenge due to its growing prevalence, difficulty to diagnose, and complex pathogenesis. It is necessary to identify an effective non-invasive and inexpensive biomarker for the early diagnosis, prognosis, and staging of NAFLD to overcome liver biopsy drawbacks such as its invasiveness and high cost. Complement C3 may be useful in the identification of fibrosis in NAFLD and it may be a promising tool for predicting the worsening of liver inflammation.